IMPLEMENTASI METODE FORWARD CHAINING DALAM PENGEMBANGAN SISTEM PAKAR DIAGNOSIS AWAL DEMAM BERDARAH (DBD) STUDI KASUS PUSKESMAS BELIDA DARAT - Wijaya, Khana; Kartina, Riza; H, Nur Aini (Jusikom : Jurnal Sistem Komputer Musirawas, 2024)
In the current era of globalization, computer technology is widely used, including in government agencies, one of which is in health agencies. The Belida Darat Community Health Center currently does not have an application for diagnosing disease, because the diagnosis is still manual and there is no comparison tool between the results of conventional diagnosis and an expert system, so that the accuracy of the doctor's decision making can be maximized, the diagnosis process takes a long time. queue number first and wait to get a call to the general poly room. This application was created so that there are no misdiagnoses and to make it easier for the public to find out early about the disease they are suffering from and so that they are not delayed in getting treatment because a doctor or expert has limited time, considering the public's ignorance or lack of information regarding the symptoms of Dengue Hemorrhagic Fever (DHF). Dengue Hemorrhagic Fever (DHF) is a disease caused by the dengue virus and spread by the Aedes Aegepty mosquito which is accompanied by bleeding manifestations and tends to cause shock and death. To overcome this problem, an expert system is needed to help the diagnosis process more easily and quickly. This expert system uses the forward chaining method. The research method used is the descriptive method, the application that the researchers built is an Android-based expert system application that can be used by the public.